Establishment of Effective Differentiation Protocols for Insulin-Producing Cells using a New 3D Culture System from Adipose-Tissue derived Mesenchymal Stem Cell. (July 2018) - Saito, Yu; Rui, Feng; Takasu, Chie; Ikemoto, Tetsuya; Iwahashi, Shuichi; Teraoku, Hiroki; Morine, Yuji; Imura, Satoru; Shimada, Mitsuo
Abstract : Background: We have reported a new effective protocols to generate insulin-producing cells (IPCs) from adipose derived mesenchymal stem cells (ADSCs) in rats using the new cell culture system with 3D scaffold named 'compound X' and xeno-antigen free reagents (ESOT 2017). The aim of this study is to clarify effectiveness of a new 3D culture plate on differentiation of human ADSCs (hADSC) to functional IPCs. Materials and Methods: IPCs were generated from hADSCs (Thermo Fisher Scientific, USA) using our established 2-step protocol with adding 1mM varproic acid which concerns pancreatic lineage. We have also investigated the 3D culture system with 3D scaffold named 'compound X*'. Furthermore, a new 3D culture plate with Elplasia® (Kuraray Co., LTD, USA), which enables us to produce a large quantities of cell spheres. Then, cell quality (cell diameter, cell viability, hormonal expression, etc.) and glucose response were investigated. Results: Our established 2-step protocol with HDACi addition accelerated differentiation duration (38 days vs 21 days, p<0.05, compared to control medium; without varproic acid). IPCs derived with'compound X' formed larger cell clusters (diameter of the cells, compared to control; without 'compound X' medium, p<0.01), showed better cell viabilities (compared to control; without 'compound X' medium, p<0.01). IPCs with Elplasia® also showed better cell viability, and higher stimulation index (1.7 vs. 2.0, control vs. Elplasia®, p<0.05). Immunohistochemistry of IPCs with Elplasia® showed strong insulin expression without central necrosis. Conclusions: The established our new 2-step protocol with a new 3D culture system could be effective for clinical transplantation for type-I DM. * The name of this compound cannot be disclosed due to the intellectual property right. Figure. No caption available.